Narzędzia wspomagające zarządzanie wiedzą o kliencie - Porębska-Miąc, Teresa (Customer Knowledge Management Support Tools, 2006)
According to Peter Drucker knowledge ¡s the only meaningful economics resource. The knowledge about individual customers is the fundamental foundation of Customer Relationship Management. This paper presents tools used l'or customer knowledge management, particularly Data Mining techniques, which may be placed into two categories. Predictive models use previous customer interactions to predict future events, and segmentation techniques arc used to place customers with similar behaviors and attributes into distinct groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 127-140